2004
DOI: 10.1093/jac/dkh283
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure of infected human endometrial epithelial cells to penicillin in vitro renders Chlamydia trachomatis refractory to azithromycin

Abstract: Thus, this study provides evidence at the cellular microbiology level in vitro for mechanisms that could exist in vivo to create sustained, but perhaps clinically inapparent inflammation, which might eventually lead to conditions such as silent pelvic inflammatory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 31 publications
4
59
0
Order By: Relevance
“…Additionally, shedding was undetectable immediately after AMX stress but resumed thereafter in all mice receiving AMX alone (persistently infected controls), as previously observed (4). Taken together, these data suggest that persistent/stressed chlamydiae are more resistant to AZM in vivo, as reported in cell culture (5).…”
supporting
confidence: 84%
“…Additionally, shedding was undetectable immediately after AMX stress but resumed thereafter in all mice receiving AMX alone (persistently infected controls), as previously observed (4). Taken together, these data suggest that persistent/stressed chlamydiae are more resistant to AZM in vivo, as reported in cell culture (5).…”
supporting
confidence: 84%
“…Problems associated with persistent chlamydial growth include the possibilities that it (i) permits immune evasion (6), (ii) provides a reservoir of bacteria that can be reactivated when conditions in the infected microenvironment are permissive (9,10), and (iii) may underlie the recalcitrance of chlamydiae to some commonly used antibiotics (11,12,39,60). In this study, we explored the effects of the specific IDO1 inhib- We hypothesize that the mechanism underlying the ability of L-1MT to rescue C. trachomatis from IFN-␥-mediated persistence, while limiting the productive multiplication of the bacterium, involves the temporal depletion of tryptophan (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about chlamydial persistence in response to tetracycline treatment, it has been noted that persistence to one antibiotic may impact upon the susceptibility of Chlamydia to another. For example, it has been found that when persistence is induced by penicillin treatment, azithromycin resistance can result, despite a previously high degree of susceptibility (Wyrick & Knight, 2004). Incidentally, the patients carrying IU824 and IU888 had both previously been treated with other antibiotics (erythromycin and cephalosporin in addition to tetracycline) for their respective infections, so this might have contributed to the in vivo tolerance of these isolates to tetracycline treatment.…”
Section: E O'neill and Othersmentioning
confidence: 99%